A new, narrowly endemic species of Blumenbachia (Loasaceae subfam. Loasoideae) from Brazil - Henning, Tilo; de Oliveira, Samuel Siriani; Schlindwein, Clemens; Weigend, Maximilian (Phytotaxa, 2015)
The genus Blumenbachia is restricted to Southern South America and comprises 10 species. Within that genus, monophyletic B. sect. Blumenbachia is a clearly delimited group of four previously known species. Here, a new species from Minas Gerais, Brazil, is described. Blumenbachia amana differs from the known species in ovoidal (versus spherical) capsules and in the unique combination of the inflorescence characters of B. insignis with the leaf morphology of B. latifolia, while approaching the flower size of B. catarinensis. Like all its close allies, the new species is facultatively autogamous, but pollinated by a highly specialized pollinator in the wild. It is geographically isolated from the other species and only known from two collections sites.